PENGARUH TERAPI KOGNITIF DAN TERAPI PSIKOEDUKASI KELUARGA TERHADAP TINGKAT ANSIETAS KLIEN KANKER: Effect of Cognitive Therapy and Family Psychoeducational Therapy On Anxiety Level of Cancer Clients - Madepan Mulia (LPPM STIKES Pemkab Jombang, 2021)
Introduction: Cancer is a group of diseases characterized by the uncontrolled growth and spread of abnormal cells that can lead to death. The physical impact caused by cancer will affect a person's psychological condition, causing psychosocial problems. Purpose: This study aims to determine the effect of cognitive therapy and family psychoeducation therapy on the anxiety level of cancer clients at the Regional General Hospital (RSUD) Dr. Hi. Abdul Moeloek, Lampung Province. Methods: This study used a quasi-experimental design with pre-post test control group with a total sample of 35 people for each group. The instrument used was hamilton anxiety rating scale (HARS). The analytical test used was repeated ANOVA test and independent t-test. Results: The results showed that cancer client anxiety decreased significantly (p value <0.05) after receiving nurse nursing action, but after being given cognitive therapy and family psychoeducation therapy, it decreased significantly than after receiving nurse nursing action. Conclusion: The implication of this research is that cognitive therapy and family psychoeducation therapy reduce the anxiety level of cancer clients, so that the hospital can add interventions related to psychosocial problems, especially for cancer clients who experience anxiety at the Regional General Hospital (RSUD) Dr. Hi. Abdul Moeloek, Lampung Province.